Disparity in Criminal Convictions Against Perpetrators of Criminal Acts of Circulation of Alcoholic Beverages Without Distribution Permits - Simarmata, Anthony; Iyah Faniyah (Master of Law Program, Ekasakti University, 2023)
Supervision and Control of Alcoholic Beverages is regulated in Presidential Regulation Number 74 of 2013 concerning Control and Supervision of Alcoholic Beverages. For the area in this case in Padang City, Control and Supervision of Alcoholic Beverages is regulated in Padang City Regional Regulation Number 8 of 2012 concerning Supervision, Control and Prohibition of Alcoholic Beverages. Based on the Regional Regulation that every circulation of alcoholic beverages must have a permit. In the case reviewed in 2 rulings, the perpetrator distributed alcoholic beverages without a distribution permit. The case has been decided by Decision Number 125/Pid.Sus/2020/PN.Pdg and Decision Number 245/Pid.Sus/2020/PN.Pdg. In the judge's decision, there is a disparity in the verdict. The problem studied is First, What is the Disparity in Criminal Verdicts Against Perpetrators of Criminal Acts of Circulation of Alcoholic Beverages Without Distribution Permits in Decisions Number 125/Pid.Sus/2020/PN.Pdg and Number 245/Pid.Sus/2020/PN.Pdg? Second, How is the judge's consideration in sentencing the perpetrators of the crime of circulating alcoholic beverages without a distribution permit in Decisions Number 125/Pid.Sus/2020/PN.Pdg and Number 245/Pid.Sus/2020/PN.Pdg? The specifics of this study are descriptive analytical. The approach used in this study is a normative juridical approach by conducting in-concreto legal research. The data used in this study are secondary data. All secondary data in the form of primary, secondary and tertiary legal materials obtained from the results of literature research / document studies are then compiled and analyzed qualitatively, and presented in qualitative descriptive form. Based on the results of the study, the discussion andanalysis concluded, First, the Criminal Disparity of Judgments Number 125/Pid.Sus/2020/PN.Pdg and Number 245/Pid.Sus/2020/PN.Pdg is illustrated through the similarity in the indictment articles given to the defendants in both judgments and there are differences in the prison sentences imposed on each defendant. Second, the judge's consideration in sentencing the perpetrators of the crime of circulating alcoholic beverages without a distribution permit in Decisions Number 125/Pid.Sus/2020/PN.Pdg and Number 245 / Pid.Sus / 2020 / PN.Pdg includes juridical considerations, namely: relating to the elements of the article charged, witness statements, statements of the defendant evidence, and expert statements and non-juridical considerations, namely: matters related to the history and condition of the defendant.